ANALISIS EKONOMI BISNIS SYARIAH INDUSTRI PARIWISATA DAN PERHOTELAN DI KEPULAUAN SERIBU DKI JAKARTA - Tia; Thahir, Andi; Rahmahwaty (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2024)
The Syariah Hospitality and Tourism Industry of the Administrative Regency located in the Kepulauan Seribu, DKI Jakarta, conducted research to analyze the influence of conditions, services, governance, access, socio-cultural and tourism impacts on tourist visits to the Kepulauan Seribu.  The method in this research uses an Explorative Research Design which is descriptive bottom-up, the researcher uses transparent, objective insights and thoughts and does not use an idealistic view in obtaining primary data from correspondents in conducting in-depth interviews accompanied by filling in a research questionnaire and the model used is Regression.  double linear. Partially, the only variables influenced by the research results are socio-cultural and tourism impacts.  Meanwhile, research simultaneously shows that all variables consisting of tourism conditions, tourism services, tourism management, tourism access, social culture, as well as the impact of Sharia-based tourism and hotels influence the satisfaction of tourists visiting Kepulauan Seribu tourism.